EDUKASI MANAJEMEN KEUANGAN UNTUK MASYARAKAT DESA DALAM RANGKA KEMANDIRIAN EKONOMI DESA MELALUI PROGRAM CINTA, BANGGA, DAN PAHAM RUPIAH - Lisa Martiah Nila Puspita; Pratana Puspa Midiastuty; Herawansyah Herawansyah; Fadila Cahya Farhanivv; Wildan Alkhairi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Financial literacy remains a critical challenge for rural communities in Indonesia, including in Panca Mukti Village, Pondok Kelapa District, Central Bengkulu Regency. The 2025 National Survey of Financial Literacy and Inclusion (SNLIK) recorded a persistent gap between urban (70.89%) and rural (59.60%) financial literacy. This community service program aimed to enhance villagers’ awareness and understanding of the use and management of quality Rupiah currency through the implementation of the “Love, Pride, and Understand Rupiah” initiative of Bank Indonesia. The activity was held on 24 July 2025 at the Panca Mukti Village Office and attended by 36 participants consisting of village officials and community members. The methods included socialization and counseling, interactive lectures, discussion, and practical demonstration supported by a resource person from the Bank Indonesia Representative Office of Bengkulu Province. The program covered three main pillars: Love Rupiah through authentic-currency recognition and money care using the 5J principle (Do Not Fold, Mark, Staple, Crumple, or Wet) and the 3D method (Look, Feel, Hold up to Light); Pride Rupiah as a symbol of national sovereignty; and Understand Rupiah in its economic functions. The results showed an increase in participants’ understanding of maintaining Rupiah quality and smart financial management, with high enthusiasm and commitment to apply the 5J principle in daily life and educate their families. Collaboration among Universitas Bengkulu, Bank Indonesia, and the village government became the key factor in the success and sustainability of the program in promoting village economic independence.